IMPROVING STUDENTS’ VOCABULARY USING REALIA - Purnamasari, Ratih; Regina, Regina; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research aimed to improve students’ vocabulary using realia to class VII F students of SMP Negeri 1 Sungai Raya in Academic Year 2017/2018. This research was conducted based on the problems found in the classroom. It was found that students had difficulties in understanding on meaning of words, spelling and pronunciation. This research was conducted through a Classroom Action Research in two cycles to 32 students of class VII F. In collecting the data, the researcher used observation and measurement technique. The tools of collecting data were observation checklist, field notes and test. The qualitative data were analyzed using the following procedure: organizing the data, describing the data and building interpretation. For the quantitative data were analyzed by finding and comparing the mean score of the test in cycle 1 and cycle 2. Based on the findings in this research, it was found that using realia in teaching and learning improved students’ understanding on meaning of words, ability in spelling and ability in pronuncing the words. Besides, the presence of the things interests the students in teaching and learning in the classroom. Keywords: Improve, Vocabulary, Realia.